UPTD SMP Negeri 2 Bangkalan Dance Extracurricular Management Strategy in Achieving Student Achievements - Hadiyanto, Ach. Ramandhani Pri; Warih Handayaningrum (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This study aims to examine the dance extracurricular management strategy in achieving student achievements at UPTD SMP Negeri 2 Bangkalan in implementing management strategies. This research method uses a qualitative approach. Data collection techniques include observation, documentation, and interviews. Miles and Huberman's data analysis includes data reduction, data visualization, and drawing conclusions. The research findings describe the dance extracurricular management plan of UPTD SMP Negeri 2 Bangkalan, which consists of three main strategies: (1) Preserving art; (2) Carving out achievements; and (3) increasing interest in talents. Based on the research findings, it can be concluded that students' success in achieving goals through dance extracurricular involvement at UPTD SMP Negeri 2 Bangkalan is influenced by a comprehensive management strategy so that the achievements obtained can be used by students to register for the next level of school through the achievement path